Quality of life from cytoreductive surgery in advanced ovarian cancer: Investigating the association between disease burden and surgical complexity in the international, prospective, SOCQER‐2 cohort study. (10th January 2022) - Sundar, Sudha; Cummins, Carole; Kumar, Satyam; Long, Joanna; Arora, Vivek; Balega, Janos; Broadhead, Tim; Duncan, Tim; Edmondson, Richard; Fotopoulou, Christina; Glasspool, Ros; Kolomainen, Desiree; et al.
Abstract: Objective: To investigate quality of life (QoL) and association with surgical complexity and disease burden after surgical resection for advanced ovarian cancer in centres with variation in surgical approach. Design: Prospective multicentre observational study. Setting: Gynaecological cancer surgery centres in the UK, Kolkata, India, and Melbourne, Australia. Sample: Patients undergoing surgical resection (with low, intermediate or high surgical complexity score, SCS) for late‐stage ovarian cancer. Main Outcome Measures: Primary: change in global score on the European Organisation for Research and Treatment of Cancer (EORTC) core quality‐of‐life questionnaire (QLQ‐C30). Secondary: EORTC ovarian cancer module (OV28), progression‐free survival. Results: Patients' preoperative disease burden and SCS varied between centres, confirming differences in surgical ethos. QoL response rates were 90% up to 18 months. Mean change from the pre‐surgical baseline in the EORTC QLQ‐C30 was 3.4 (SD 1.8, n = 88) in the low, 4.0 (SD 2.1, n = 55) in the intermediate and 4.3 (SD 2.1, n = 52) in the high‐SCS group after 6 weeks ( p = 0.048), and 4.3 (SD 2.1, n = 51), 5.1 (SD 2.2, n = 41) and 5.1 (SD 2.2, n = 35), respectively, after 12 months ( p = 0.133). In a repeated‐measures model, there were no clinically or statistically meaningful differences in EORTC QLQ‐C30 global scores between the three SCS groups ( p = 0.840), but there was a small statistically significant improvement in all groups over time ( p < 0.001). The high‐SCS group experienced small to moderate decreases in physical ( p = 0.004), role ( p = 0.016) and emotional ( p = 0.001) function at 6 weeks post‐surgery, which resolved by 6–12 months. Conclusions: The global QoL of patients undergoing low‐, intermediate‐ and high‐SCS surgery improved at 12 months after surgery and was no worse in patients undergoing extensive surgery. Tweetable Abstract: Compared with surgery of lower complexity, extensive surgery does not result in poorer quality of life in patients with advanced ovarian cancer. Tweetable Abstract: Compared with surgery of lower complexity, extensive surgery does not result in poorer quality of life in patients with advanced ovarian cancer.